(untitled) (Innovative professional education, 2025)
In order to develop a technology for the formation of professional competence (PC) of students based on the theory of activity and contextual learning, a new pedagogical technology was modeled – the technology of online management of the development of each student’s PC by performing tasks in a project team, decomposed from relevant professional ones. Its compliance with the criteria of pedagogical technologies and high efficiency were substantiated